STREAM -didaktik i förskola med litteracitet(er) i fokus - mellan att öppna för det okända och söka efter det kända - Helena Hansen; Ann-Christine Vallberg Roth (Dalarna university, 2024)
The study in this paper aims to contribute knowledge about what characterizes STREAM didaktik in preschool based on a theory-informed teaching arrangement in an ULF[i] network. The study is guided by the question: What can characterize STREAM didaktik in preschool with a focus on literac/y/(ies) in what and who/which questions? Theoretically, the study is connected to three main concepts: STREAM, didaktik and literacy. The material consists of 85 documents, totalling 14, 200 words and 2.5 hours of film focusing on planning and conducting teaching in preschool. The knowledge contribution is: 1) STREAM didaktik with literacy(s) in focus appears as a relation between general didaktik and subject didaktik in preschool, 2) STREAM didaktik with literacy(s) in focus can also be seen as a bridge between opening to the unknown and searching for the known in a movement between planned and spontaneous teaching in preschool, and 3) STREAM didaktik with focus on literacy(s) in what and who/which questions can be tried in terms of STREAM actors. [i] ULF är en förkortning av Utbildning, Lärande och Forskning (https://www.ulfavtal.se/). Länk till vårt ULF-nätverk